PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN IPS KELAS IV DI SD/MI - Jannah, Miftahul (LPPM STKIP PGRI Bandar Lampung, 2020)
This study aims to develop a plan for the implementation of Class IV social studies learning at SD / Mi. This research is a research and development or Research and Development (R&D). Data analysis starts from the stages of data collection, data presentation, and data verification. Based on the results of the study, it can be concluded that the use of the lesson plan (RPP) has a positive impact in supporting efforts to improve learning outcomes for fifth grade students in elementary schools.